In Vitro and Ex Vivo Biofilm-Forming Ability of Rhinocladiella similis and Trichophyton rubrum Isolated from a Mixed Onychomycosis Case - Polyana de Souza Costa; Maria Eduarda Basso; Melyssa Negri; Terezinha Inez Estivalet Svidzinski (Journal of Fungi, 2023)
Infections caused by biofilm-forming agents have important implications for world health. Mixed infections, caused by more than one etiological agent, are also an emerging problem, especially regarding the standardization of effective diagnosis and treatment methods. Cases of mixed onychomycosis (OM) have been reported; however, studies on the microbial interactions between the different fungi in biofilms formed on nails are still scarce. We describe a case of mixed OM caused by the dermatophyte Trichophyton rubrum and the black yeast-like fungus Rhinocladiella similis. Identical growths of both fungi were observed in more than 50 cultures from different nail samples. Additionally, both species were able to form organized single and mixed biofilms, reinforcing the participation of both fungi in the etiology of this OM case. R. similis seemed to grow faster during the process, suggesting that T. rubrum benefits from biofilm development when in combination. Moreover, the biofilm of the Rhinocladiella isolate exhibited exacerbated production of the extracellular matrix, which was not observed with that of a Rhinocladiella reference strain, suggesting that the isolate had natural abilities that were possibly perfected during development in the nail of the patient.